Research on Speed and Position Detection Technology for Train Operation Control System Based on Multi-Source Information Fusion - YANG Chongfu (Kongzhi Yu Xinxi Jishu)
The conventional train positioning technology primarily relies on wheelset speed measurement and distance measurement, resulting in a single source of locating data that is susceptible to factors such as wheelset wear, wheel idling, and wheel sliding. This technology yields positioning results with significant errors, compromising the safety of train operation. To deal with this issue, this paper investigates the speed measurement and positioning technologies employed in the next-generation LKJ train operation control system. Key aspects studied include automatic alignment upon departure at originating stations, automatic correction of wheel diameter, elimination of accumulative errors in distance measurements, alerts for wheel idling and sliding, and error rectification. The paper presents a novel train locating solution that focuses on heterogeneous multi-channel fusion for speed and distance detection. This approach integrates radar speed sensors, BeiDou differential positioning, and balise technologies with the existing wheelset speed measurement technology. Results of experiments conducted on real trains indicated that with the implementation of the proposed technology, train positioning errors were reduced from ±2.0% to ±1.5%, and the positioning accuracy reached up to ±5 cm and operational control precision within ±30 cm—thereby facilitating precise control over trains and enhancing traffic capacity.